The Naomi Cook Book: A Narrative of Canadian Jewish Integration - Trojan, Gesa (Canadian Jewish Studies / Études juives canadiennes, 2021)
Canadian Jewish integration was a social process that took place in the political sphere, but was also driven by everyday practices such as preparing and consuming food. Despite this, Jewish food history and the history of Canadian Jewish integration have been mostly investigated separately. This essay ties in with the work of Franca Iacovetta et al. and Donna Gabbaccia, who examined ethnic identity politics and food history in Canada and the USA as interrelated fields. To add to this research, this paper examines a Jewish community cookbook as a moment of Jewish-Canadian integration. By analyzing the Naomi Cook Book, published from 1928 to 1960 by Hadassah-WIZO in Toronto, this paper offers the alternative of exploring integration history as a history of everyday life. It argues that the cookbook is more than a recipe collection. By presenting specific ingredients, menus, and advertisements, it is promoting a narrative of Anglophone Canadian Jewish integration to a larger sociocultural frame of North American consumer culture. In doing so, it presents the history of Jewish-Canadian integration not as a linear sequence of steps on a ladder leading to completion, but as a process with both new and recurrent challenges, contradictions, and contestations.